Analysis of Practical Mandarin during Short-term Learning and Traveling Program in China among Non-Chinese Students - Yong, Ying Mei; Cheng, Ching Yee; Lee, Chia Kuang (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
Practical Mandarin among non-Chinese speakers is essential in learning Mandarin as foreign language. It is observed that the actual use of a foreign language differs greatly from classroom learning. For instance, a non-Chinese student who travels to China will perform differently in actual Mandarin speaking situations. Previous research substantiated that foreign language experience enable learners to improve their communication competencies in every domain. Studies have been carried out in this area but the language performances of Mandarin learners in real speaking circumstances such as travelling, has not raised much scholarly interest. Therefore, this study aims to determine the effectiveness of practical Mandarin among non-Chinese students after they attended the Mandarin courses. A total of 10 students from Universiti Malaysia Pahang who have joined a short-term learning and travelling program in China have been recruited to fill out a set of questionnaire. It examines their actual use of practical Mandarin after practicing their Mandarin in China. The findings are presented in the form of descriptive statistics such as topic of practical Mandarin, target audience, types of mastered language skills, challenges in practical Mandarin and selfevaluation of practical Mandarin. Accordingly, this article offers useful suggestions and strategies to enhance practical Mandarin among non-Chinese students.